The Association between Clean and Healthy Behavior in a Household and the Incidence of Diarrhea in Children Under Five-Years Old in the Territories of Puskesmas Ngoresan - I Kadek Ludi Junapati; Rifai Hartanto; Bhisma Murti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Backgrounds: Diarrhea is one of the highest cause of mortality and morbidity in children, especially under five-years old. Outbreak of diarrhea also often happen with high Case Fatality Rate (CFR). Diarrhea can be prevented if the community can apply clean and health behavior. The purpose of this research is to analyze the correlation of clean and health behavior in a household with the incidence of diarrhea in children under five-years old. Methods: This research was an observational epidemiology research with the case control approach. It was held in May-June 2014 in the territories of Puskesmas Ngoresan Jebres. Sampling had been done by fixed-disease sampling, and the selection was done by checking the inclusion and exclusion criteria of the study sample. Data was collected using questioner and independent interview to the respondent. Data obtained by 60 subjects and analyzed by Chi Square Test. Results: Based on the result of Chi Square test, there was a significant difference between the group of people with clean and health behavior in a household with the incidence of diarrhea, whereas the value of p (<0,001) < 0,05. Out of eight indicators, there are four indicators which have a significant correlation with the incidence of diarrhea, those are the use of clean water (p value <0,001), waste management (p value <0,001), use of floor (p value <0,001) and use of latrines (p value 0,042). Conclusions: Based on this research, there is a significant difference between clean and health behavior in a household with the incidence of diarrhea in children under five-years old.Keywords: Diarrhea, Children Under Five-Years Old, Clean and Healthy Behavior in a Household.Backgrounds: Diarrhea is one of the highest cause of mortality and morbidity in children, especially under five-years old. Outbreak of diarrhea often happen with high Case Fatality Rate (CFR). Diarrhea can be prevented if the community can apply clean and healthy behavior. The purpose of this research is to analyze the correlation associationof between clean and healthy behavior in a household with and the incidence of diarrhea in children under five-years old. Methods: This research was an observational epidemiology research with the case control approach. It was held in May-June 2014 in the territories of Puskesmas Ngoresan Jebres. Sampling has been done by fixed-disease sampling, and the selection was done by checking the inclusion and exclusion criteria of the study sample. Eight criteria were used to assess clean and healthy behaviour. Those are: use of clean water, waste management, use of floor, use of latrines, nutritional status, teeth and mouth hygiene, exclusive breastfeeding, and hand hygiene. Data were collected using questionnaire and independent interview to the respondents. Data obtained from 60 subjects and were analyzed by chi-square test. Results: Based on chi-square test, out of eight indicators, there are four indicators that were have significant correlation associated with the incidence of diarrhea, those are the use of clean water (p value <0,001), waste management (p value <0,001), use of floor (p value <0,001) and use of latrines (p value: 0,042). Whereas other four indicators have no significant correlation were not associated with the incidence of diarrhea, those are nutritional status (p value: 0,154), teeth and mouth hygiene (p value: 0,326), exclusive breastfeeding (p value: 0,443), and hand hygiene (p value: 1,000). Conclusions: Based on this research, among eight indicators there are were four indicators of clean and healthy behaviour in a household that that have significant associated with the incidence of diarrhea in children under five-years old, those are the use of clean water, waste management, use of floor and use of latrines. Keywords: Diarrhea, Children Under Five-Years Old, Clean and Healthy Behavior in a Household.